Avaliação de Listeria monocytogenes como controle de qualidade no processamento de carnes - Monteiro, Francielli Casanova (2015)
The production of pork in Brazil has taken a great leap in recent years, in quantitative and qualitative. This allowed position Brazil among the main active worldwide in the field of pig farming. The guarantee of the safety of food depends on the ability of industries to minimise the contamination of food by pathogenic micro-organisms, especially during processing and storage, and to ensure that the guarantee will continue to be maintained. Among the existing pathogens, stands out Listeria monocytogenes, which is an important pathogen of food origin emerging and causing localized infections and generalized, leading the individual to death. In this sense, the objective of this study was to evaluate the health quality of the production process from an abattoir-fridge of pigs, as the presence of L. monocytogenes. Initially were standardized methods for the application of PCR analysis and sequencing of subsequently applied in the samples collected. Two samples were collected in a fridge that slaughter pigs located in the region of Campos Gerais - PR. Also it was found that the deadlines and costs presented by private laboratories Brazilians, making a comparison with the molecular technique. The number of positive samples of seunda collection was superior to that of the first, 10 and 3 respectively. With the sequencing was possible to observe that the source of contamination is in the sector of triparia. It was also possible to observe that few laboratories have the PCR as a method of diagnosis, and it has been proved that the technique can be a great alternative to present economic and feasible for meat industry.